Hormonal Control of Medial–Lateral Growth and Vein Formation in the Maize Leaf - Robil, Janlo M. (Archīum Ateneo, 2023)
Parallel veins are characteristic of monocots, including grasses (Poaceae). Therefore, how parallel veins develop as the leaf grows in the medial–lateral (ML) dimension is a key question in grass leaf development. Using fluorescent protein reporters, we mapped auxin, cytokinin (CK), and gibberellic acid (GA) response patterns in maize (Zea mays) leaf primordia. We further defined the roles of these hormones in ML growth and vein formation through combinatorial genetic analyses and measurement of hormone concentrations. We discovered a novel pattern of auxin response in the adaxial protoderm that we hypothesize has important implications for the orderly formation of 3° veins early in leaf development. In addition, we found an auxin transport and response pattern in the margins that correlate with the transition from ML to proximal–distal growth. We present evidence that auxin efflux precedes CK response in procambial strand development. We also determined that GA plays an early role in the shoot apical meristem as well as a later role in the primordium to restrict ML growth. We propose an integrative model whereby auxin regulates ML growth and vein formation in the maize leaf through control of GA and CK.